PERAN EMPLOYEE AGILITY TERHADAP READINESS TO CHANGE PADA DOSEN - Nur Ainy Sadijah; Marhisar Simatupang; Florensia Nei; Epifania Margareta Ladapase; Randwitya Ayu Ganis Hemasti (Jurnal Ilmiah Global Education, 2023)
This study aims to determine the role of employee agility in the readiness to change of lecturers in carrying out merdeka belajar kampus merdeka. In this study involved 190 samples using saturated sampling technique. Test the hypothesis using simple linear regression. The scale used in this study is the employee agility and readiness to change scale. The results of the study show that there is a role for employee agility in the readiness to change for lecturers in carrying out merdeka belajar kampus merdeka. This shows that the higher employee agility will increase the readiness to channel for lecturers.